Gamificação e o impacto no ensino-aprendizagem de libras para surdos e ouvintes - Silva, Luana Gomes da (Brasil, 2023)
The work of applying content in pandemic times led to several challenges in the field of education. Teacher and student in the classroom needed to adapt to new concepts and technologies. Faced with these new challenges, how to maintain the teaching and learning potential with motivation and engagement in the classroom? Does the use of technological devices as tools to gamify activities bring a positive return? Would these strategies be effective for deaf students and hearing sign language users? To answer these questions, this work has the general objective of analyzing teaching strategies using the gamification strategy of didactic tools for use in the classroom, improving the motivation, engagement and learning of deaf and hearing students, as a theoretical pillar to contextualize the objectives of the research, we highlight authors such as Quadros, Karnopp, Ausubel, Vygotsky, Bakhtin, Murr and Ferrari to list and bring the alignments that link the arguments of this work. The method used was a literature review in the area of gamification, qualitative analysis from pre-service reports in monitoring and internship period. The results obtained point to a good result of student participation and performance, however, some caveats need to be considered so that this strategy can achieve the objectives by incorporating elements of games to the activities so that they are beyond fun.